2022
DOI: 10.3390/w14223593
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Shoreline and Land Use/Land Cover Changes in Sandbanks Provincial Park Using Remote Sensing and Climate Data

Abstract: Climate change-driven forces and anthropogenic interventions have led to considerable changes in coastal zones and shoreline positions, resulting in coastal erosion or sedimentation. Shoreline change detection through cost-effective methods and easy-access data plays a key role in coastal management, where other effective parameters such as land-use/land-cover (LULC) change should be considered. This paper presents a remotely sensed shoreline monitoring in Sandbanks Provincial Park, Ontario, Canada, from 1984 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…EO is increasingly used to monitor and detect coastlines as well as establish the degree of vulnerability, with many relevant studies identified in the relevant literature, e.g., [7,[17][18][19]. Furthermore, Geographical Information Systems (GISs) can capture, display, integrate, and analyze a large number of geospatial data, which explains their often-synergistic use with EO datasets [20][21][22].…”
Section: Overall Methodological Approachmentioning
confidence: 99%
“…EO is increasingly used to monitor and detect coastlines as well as establish the degree of vulnerability, with many relevant studies identified in the relevant literature, e.g., [7,[17][18][19]. Furthermore, Geographical Information Systems (GISs) can capture, display, integrate, and analyze a large number of geospatial data, which explains their often-synergistic use with EO datasets [20][21][22].…”
Section: Overall Methodological Approachmentioning
confidence: 99%
“…Several studies were conducted based on dynamic changes of land use and land cover with land cover change detection and supervised classification (Akyürek et al 2018;Seyam et al 2023) and accuracy assessment using the kappa coefficient (Tewabe and Fentahun, 2020;Hussain and Karuppannan, 2023), and prediction by satellite image of landsat-7 and landsat-8 using cellular automated and Markov chains (Abijith and Saravanan, 2022;Wang et al 2021). Deep learning (DL)-based method (Song et al 2021), supervised classification, NDVI method (Pande et al 2021) including field verification and Google Earth Professional (Kamel, 2020), NDWI method (Raut et al 2020), MNDWI method (Bhattacharjee et al 2021), transition matrix method (Bagwan and Sopan, 2021), post classification matrix (Kouhgardi et al 2022; Márquez-Romance et al 2022; Das and Angadi, 2022), classprior object-oriented conditional random field (COCRF) method (Shi et al 2020), maximum likelihood classifier (MLC) method (Kumar and Jain, 2020; Saini et al 2019;Sarif and Gupta, 2022), Siamese global learning framework (Zhu et al 2022), preprocessing and classification and accuracy assessment (Thakur et al 2020;Mondal et al 2021;Mondal et al 2022), using various satellite imagery such as Landsat, MODIS, Sentinel and SPOT. The advantage of Landsat satellite data is the free accessibility of multi-temporal time series since 1972 (Lu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are estimates that range from 21-760 million Mg CO 2 equivalents per year that result from this land use change, which contributes to climate change [6]. The possibility of coastal wetlands mitigating climate change has received considerable attention in recent years due to their large carbon stocks, high carbon sequestration rates, and the possibility that human activities, such as conversion and degradation, could increase greenhouse gas (GHG) emissions [7,8]. Thus, several entities have expressed a desire to manage coastal wetland blue carbon [9].…”
Section: Introductionmentioning
confidence: 99%